Criminal Justice System Reform: A Comparative Approach between European and Asian Countries - Mohammed Abdu Rehany (Edujavare Publishing, 2024)
This research conducts a comprehensive comparative analysis of criminal justice system reforms in European and Asian countries, aiming to highlight similarities, differences, challenges, and opportunities for improvement. The study examines the evolution of legal frameworks, procedural safeguards, and enforcement mechanisms within diverse historical, cultural, and normative backgrounds. Findings reveal that European countries prioritize judicial independence, human rights protection, and adherence to international legal standards. However, Asian nations exhibit varied approaches influenced by civil law, common law, and customary legal traditions. The analysis underscores the importance of upholding the rule of law, protecting individual rights, and promoting transparency and accountability within criminal justice systems. Moreover, the research emphasizes cross-regional learning, evidence-based policymaking, and continuous evaluation to address systemic challenges and foster more effective, equitable, and rights-respecting legal systems globally.